2011
DOI: 10.1084/jem.20101773
|View full text |Cite
|
Sign up to set email alerts
|

Viral persistence redirects CD4 T cell differentiation toward T follicular helper cells

Abstract: Persistent virus infection drives follicular T helper cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
354
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(393 citation statements)
references
References 54 publications
37
354
1
1
Order By: Relevance
“…Our findings complement emerging evidence showing that unique properties of different pathogens and immunization strategies imprint on T FH cells to define their unique cytokine and costimulatory profile and, ultimately, to specify antibody responses (16,(60)(61)(62). A possible distinguishing feature among pathogens is differential expression of TLR ligands, which may stimulate DCs to influence their cytokine expression and also their ability to promote T FH cell expansion.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings complement emerging evidence showing that unique properties of different pathogens and immunization strategies imprint on T FH cells to define their unique cytokine and costimulatory profile and, ultimately, to specify antibody responses (16,(60)(61)(62). A possible distinguishing feature among pathogens is differential expression of TLR ligands, which may stimulate DCs to influence their cytokine expression and also their ability to promote T FH cell expansion.…”
Section: Discussionsupporting
confidence: 76%
“…Tfh cells are a subset of activated CD4 1 T cells and are specialized to regulate B-cell-mediated humoral immunity [11,27]. Furthermore, a recent study suggested that persistent infection of virus could drive the differentiation of helper T cells to Tfh cells [28]. Although Tfh cells are linked to GC B-cell survival and the formation of long-lived plasma cells [12,29], their role in chronic inflammatory condition, especially related to persistent bacteria, has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude and duration of antigenic stimulation are known to be important determinants of the GC Tfh cell response,193 and although GC Tfh cell frequencies do not generally show a direct correlation with viral load, the increase in GC Tfh cells during chronic SIV/HIV infection is dependent on ongoing antigenic stimulation, as GC Tfh cell frequencies decline when viral replication is contained by antiretroviral therapy 168, 189, 191. Sustained LCMV replication in mice is also associated with expansion of GC Tfh cells, and here IL‐6 production has been shown to play a key role in driving Tfh cell differentiation during chronic infection 194, 195. GC Tfh cell expansion in chronic HIV‐1 infection is also associated with elevated IL‐6 production,189 but as IL‐6 is not such a potent stimulus of human CD4 + differentiation into Tfh cells, it can be speculated that upregulation of other Tfh‐differentiating cytokines, in the context of the reduction in IL‐2 expression known to occur in chronic HIV infection,196 may play a more important role in enhancing Tfh cell differentiation during HIV infection.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%